2016
DOI: 10.5430/jnep.v7n5p33
|View full text |Cite
|
Sign up to set email alerts
|

The predictors of cultural competence among new baccalaureate degree nursing graduates: Implications for nursing education

Abstract: Objective: Nurses are charged with providing quality care to all patients. In part, as a result of current and projected demographic changes in the United States, as well as the varying needs and circumstances of individual patients, nurses are faced with the challenges of providing culturally competent care. Preparing to care for a culturally diverse population begins during the teaching/learning process in the nursing curriculum. The aim of the study was to determine which teaching method(s) (stand-alone cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…Having experienced taking care of culturally diverse patients and patients belonging to special population groups as well as having attended diversity‐related training positively influence cultural competence. These findings are similar to previous studies (Dunagan ; Silvestri‐Elmore ). Situations that provide opportunities for nursing students to interact with patients from various cultures and patients belonging to special population groups are beneficial in assisting in the refinement of the students' perceptions and beliefs towards specific cultural groups.…”
Section: Discussionsupporting
confidence: 93%
“…Having experienced taking care of culturally diverse patients and patients belonging to special population groups as well as having attended diversity‐related training positively influence cultural competence. These findings are similar to previous studies (Dunagan ; Silvestri‐Elmore ). Situations that provide opportunities for nursing students to interact with patients from various cultures and patients belonging to special population groups are beneficial in assisting in the refinement of the students' perceptions and beliefs towards specific cultural groups.…”
Section: Discussionsupporting
confidence: 93%
“…Content validity for this section of the questionnaire was ensured by including questions and answer options based on published work in cultural responsiveness or based on the census data collection in Australia and Aotearoa New Zealand [9, 23, 35, 36]. For example, questions related to demographic variables such as age, gender, level of study, self-identified ethnoculture, type of program or previous cultural training were either adapted from published studies assessing self-perceived cultural responsiveness or constructed based on the literature defining important factors associated with cultural responsiveness.…”
Section: Methodsmentioning
confidence: 99%